A Genetic Algorithm Approach to the Reduction of Additive Noise in Single Trial Evoked Potentials - Pougnet, Michael J.; Lovely, Dennis F.; Parker, Philip A. (CMBES Proceedings, 2010)
A matching tool is introduced for use in noise reduction of single trial evoked potentials. Specific performance markers such as distortion and output SNR are investigated. Results show that the matching tool is able to significantly increase output SNR while reducing the effects of distortion. A new performance metric named the signal improvement quotient is also introduced. This measure represents the ratio of output SNR to distortion. It is suggested that this new metric may be a better measure of noise reduction abilities than a high output SNR. Other factors such as the limitations of the matching tool are also discussed.